Integration of Physical Activities into Guidance and Counseling Services to Enhance Students’ Emotional Well-Being - Nor Hidayah; Rizki Erdiantoro; Iis Lathifah Nuryanto (Journal of Education and Counseling (JECO), 2025)
Emotional well-being and physical activity are two essential components that support students’ holistic development. This article explores how physical activity can enhance students’ emotional well-being through guidance and counseling services. Using a literature review method, the article examines relevant studies published between 2014 and 2025. The findings indicate that emotional well-being significantly influences academic achievement, character development, and students’ social relationships. Meanwhile, physical activity not only benefits physical health but also helps reduce stress, elevate mood, and strengthen the counseling process. Integrating physical activity into guidance and counseling services has proven effective in supporting students' mental health. Therefore, collaboration among teachers, families, and school policymakers is crucial in creating an environment that promotes sustained psychological well-being and healthy lifestyles.